Amyloid-β associated volume loss occurs only in the presence of phospho-tau - Desikan, Rahul S. (2011)
The relationship between neurodegeneration and the two hallmark proteins of Alzheimer's disease, amyloid-β (Aβ) and tau, is still unclear. Here, we examined 286 non-demented participants (107 cognitively normal older adults and 179 memory impaired individuals) who underwent longitudinal MR imaging and lumbar puncture. Using mixed effects models, we investigated the relationship between longitudinal entorhinal cortex atrophy, CSF p-tau(181p) and CSF Aβ(1-42). We found a significant relationship between elevated entorhinal cortex atrophy and decreased CSF Aβ(1-42) only with elevated CSF p-tau(181p). Our findings indicate that Aβ-associated volume loss occurs only in the presence of phospho-tauin humans at risk for dementia.